Pengaruh Pola Kredit Pengadaan Bibit Terhadap Kinerja Pengembangan Sapi Potong Pada Peternak Kecil Di Provinsi Jambi - Husni Jamal (Universitas Andalas, 2007)
The research was aimed to study the influence of credit schemes in providing breeding stock on the performance of beef cattle development for smallholder farmers. The research was carried out through a survey on 183 respondents who involved the beef cattle development project. They were located in three Development Areas of Beef Cattle in Jambi Province: Singkut, Regency of Serolangun; Pamenang, Regency of Merangin; and Kuamang Kuning, Regency of Bungo. The respondents were divided into two groups of credit recipients, who received credit with FI (Full In-kind) and CC (Cash Credit) schemes. Results showed that there were more heifers obtained from CC scheme (50 %) to become acceptors of Artificial Insemination program than that of obtained from FI scheme (7 %). Birth Rate of the heifers from FI scheme (0,51 + 0,18 heads/year) was significantly lower than that from CC scheme (0,84 + 0,80 heads/year). Mortality Rate of calves from CC scheme (1,7 %) was lower than that from FI scheme (6,5,%). The number of respondents from CC scheme who planted grasses (71 %) and offered concentrate for their animals (46 %) was higher than that form from FI ( 28 % and I6 %, respectively). Respondents received CC scheme showed more positive Attitude toward Beef Cattle Development than those received FI scheme. It was concluded that CC scheme in providing breeding stocks for smallholder farmers in Jambi Province had a better influence on the performance of beef cattle development than FI scheme did. Therefore, the researcher recommended to the government to reevaluate the existence of FI scheme.